2022
DOI: 10.3390/cancers14163871
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cells with Macrophage-like Characteristics in Cancer: The Importance of Circulating Neoplastic-Immune Hybrid Cells in Cancer

Thomas L. Sutton,
Ranish K. Patel,
Ashley N. Anderson
et al.

Abstract: Cancer remains a significant cause of mortality in developed countries, due in part to difficulties in early detection, understanding disease biology, and assessing treatment response. If effectively harnessed, circulating biomarkers promise to fulfill these needs through non-invasive “liquid” biopsy. While tumors disseminate genetic material and cellular debris into circulation, identifying clinically relevant information from these analytes has proven difficult. In contrast, cell-based circulating biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 150 publications
0
35
0
Order By: Relevance
“…One veterinary study found that of 39 complete blood counts from dogs with circulating macrophage-like cells, 46% had a diagnosis of cancer (including both histiocytic and non-histiocytic origin) ( 184 ). These cells have the potential to be detectable in higher numbers than circulating tumor cells as sources of phagocytized tumor DNA ( 185 ).…”
Section: Tams In Companion Dogsmentioning
confidence: 99%
“…One veterinary study found that of 39 complete blood counts from dogs with circulating macrophage-like cells, 46% had a diagnosis of cancer (including both histiocytic and non-histiocytic origin) ( 184 ). These cells have the potential to be detectable in higher numbers than circulating tumor cells as sources of phagocytized tumor DNA ( 185 ).…”
Section: Tams In Companion Dogsmentioning
confidence: 99%
“…Whether solitary adopted cells also proliferate is unclear because migratory cells can wander away from each other instead of forming a cluster. That at least some of the adopted cells are migratory, perhaps because they retain some features of their normal precursors, follows from their presence among circulating tumor cells [30,51,52], an observation that also implies that adopted cells can retain their neoplastic phenotype for some time after leaving the tumor.…”
Section: What Would the Existence Of Adopted Neoplastic Cells Imply?mentioning
confidence: 99%
“…Circulating tumor cells (CTC), discovered a century and a half ago [74], are neoplastic cells present in the blood of patients with solid tumors and are thought to include the precursors of metastases [75]. Paradoxically, a fraction or, in some cases, most of CTC released by some non-hematological tumors, such as melanoma, breast, ovarian, and pancreatic cancers, were found to carry CD45, a protein whose expression is normally restricted to bone-marrow derived cells [30,51,[76][77][78]. Hence, these cells (CTC-CD45) were viewed as a persistent artifact until an appeal to give them a closer look [77] revealed that they indeed exist [79] and that their concentration inversely correlates with the survival of patients with pancreatic cancer [30,51].…”
Section: Puzzling Circulating Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer is characterized by the abnormal and uncontrolled proliferation of cells, which possess the ability to metastasize or invade other parts of the body [ 1 , 2 ]. The invading cells form a subset of neoplasms, which either form a tumor lump or a diffusely distributed cell population [ 3 , 4 ]. Chemotherapy is one of the common modalities of cancer treatment.…”
Section: Introductionmentioning
confidence: 99%